Seed yield, nutrient balance and economics of mungbean cultivation as influenced by different nutrients management under AEZ-28 - Jahan, MAH S; Sarkar, MAR; Barma, NCD; Mondal, MNA; Ferdousi, MNS (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at Regional Wheat Research Centre of the Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh for 2 consecutive years during 2007 and 2008 to find out the optimum nutrient management practice for seed yield, nutrient balance and economics of mungbean. Twelve nutrient management treatments were tested in RCBD with 3 replications. Treatments were without CRI T1=HYG (0-24-40-48-24-3-1.2), T2=MYG (0-20-36-40-20-2-1), T3=IPNS (5000-9-37-36-21-3-1.2), T4=STB (0- 20-36-40-22-2-1), T5=FP (0-6-5-4-0-0-0), T6=CON (0-0-0-0-0-0-0) and with CRI T7=HYG+CRI, T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI kg ha-1 CDNPKSZnB for mungbean. The maximum seed yield of mungbean was obtained from STB+CRI (1.57 t ha-1) followed by IPNS+CRI (1.54 t ha-1), STB (1.54 t ha-1), IPNS (1.52 t ha-1), HYG+CRI (1.44 t ha-1) and HYG (1.41 t ha-1) in 2007. Similar trend was found in 2008. Numerically higher yield and yield contributing parameters were noticed in CRI plots than without CRI. N and K balance were found negative in all the treatments. P, S, Zn and B balance were found positive in case of HYG, MYG, IPNS and STB along with or without CRI nutrient managements. While in case of FP and CON, the balance was shown almost negative. The maximum gross return and margin was obtained from STB+CRI followed by STB. Slightly higher BCR (3.00) was recorded from STB followed by STB+CRI (2.91). Bangladesh J. Agril. Res. 40(1): 77-93, March 2015